2020
DOI: 10.1177/0886260520943722
|View full text |Cite
|
Sign up to set email alerts
|

Do Trajectories of Sensation Seeking Vary by Sex and Child Maltreatment Subtypes?

Abstract: Child maltreatment and elevated sensation seeking are associated with a wide range of negative outcomes. Longitudinal data from a study of Puerto Ricans living in two sociocultural contexts were used to determine whether child maltreatment subtypes, sex, or sociocultural context relate to trajectories of sensation seeking. Participants were 2,489 individuals from the Boricua Youth Study (48.5% girls) living in New York and in Puerto Rico (PR; 5–15 years old at Wave 1). Subtypes of child maltreatment were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…This may indicate that mid to late adolescence are not periods of the life-course when the cognition of JIY may be most apt to change. Considering that event occurrences in the life-course, like traumatic stress exposure, may alter these cognitive constructs (Brady & Donenberg, 2006; Imas et al, 2018; Sharkey et al, 2012; Sussman et al, 2020), yet very little variance in patterns of development was observed here in the trajectory models themselves, it may be demonstrative of a similar lack of malleability in dual systems constructs when exposed to psychosocial interventions during mid to late adolescence for this population. This may provide some indication that such programming may be more effective when targeting younger adolescents.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This may indicate that mid to late adolescence are not periods of the life-course when the cognition of JIY may be most apt to change. Considering that event occurrences in the life-course, like traumatic stress exposure, may alter these cognitive constructs (Brady & Donenberg, 2006; Imas et al, 2018; Sharkey et al, 2012; Sussman et al, 2020), yet very little variance in patterns of development was observed here in the trajectory models themselves, it may be demonstrative of a similar lack of malleability in dual systems constructs when exposed to psychosocial interventions during mid to late adolescence for this population. This may provide some indication that such programming may be more effective when targeting younger adolescents.…”
Section: Discussionmentioning
confidence: 71%
“…Prevalence of PTSD among JIY has been observed at rates varying between 5%-18% (Brosky & Lally, 2004;Kerig et al, 2012;McNair et al, 2019). Exposure to traumatic stress has been identified as a risk factor predicting both high levels of sensation-seeking and also diminished impulse control (Brady & Donenberg, 2006;Imas et al, 2018;Sharkey et al, 2012;Sussman et al, 2020). Characteristics of PTSD underpin these relationships and the disorder may provide a useful clinical marker of potential dysfunction in development of dual systems model constructs.…”
Section: Ptsd As a Potential Driver Of Differences In Dual Systems De...mentioning
confidence: 99%
See 1 more Smart Citation